2004
DOI: 10.1191/0267659104pf718oa
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of coated extracorporeal circuits: a review of novel technologies

Abstract: Coating of extracorporeal circuits may be a solution to prevent adverse effects induced by the contact of blood elements and proteins with foreign surfaces. This paper reviews the recent novel coating technologies and compares their documented in vitro and ex vivo advantages under the clinical setting. Data presented have also been supported by postclinical biomaterial research to verify biocompatibility and hemocompatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Studies with similar objectives and methods have often yielded contradictory results, which suggest that the specific response mechanisms of CPB may vary between patients [23].…”
Section: Resultsmentioning
confidence: 99%
“…Studies with similar objectives and methods have often yielded contradictory results, which suggest that the specific response mechanisms of CPB may vary between patients [23].…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, there are several reports on the impact of coated oxygenators on the immune response. It was suggested that leukocyte levels increased and platelet levels decreased in both phosphorylcholine-coated and uncoated oxygenators with regard to baseline values during induction of anaesthesia 8,9…”
Section: Discussionmentioning
confidence: 99%
“…20 Despite early promise as a means of reducing the inflammatory response to surgery and subsequent organ damage, the evidence of the clinical value of leukocyte filtration remains equivocal. 21 One of the limitations affecting almost all studies investigating the inflammatory response to CPB is that the patient populations are small and include uncomplicated cases.…”
Section: Discussionmentioning
confidence: 99%